The Influence of the Dynamics of Political Life within the Framework of the Unitary State of the Republic of Indonesia - Beatrice Angelica; Callista Ciunta; Cellyn Winata; Felicia Tjenggo; Felysia Kosasih; Joventy Lim; Michelle Faustibe Zhu; Rolib Sitorus (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the modern era or digital era in the context of the Unitary State of the Republic of Indonesia, a study was conducted that aims to determine the influence of the digital era on the dynamics of political life, as well as to determine efforts to face the challenges of the presence of social media or the internet in the political life of the Unitary State of the Republic of Indonesia. The research method used is the literature study method. The results of the study show that the impact of technological developments can be something positive, such as increasing the efficiency of election implementation. The results achieved are that digitalization can increase transparency and public trust in elections, with the note that there is a need for an even digital infrastructure and HR readiness. In addition, the role of the younger generation is very important because it will support the change from traditional elections to utilizing technology. Because if utilized properly, the implementation of online voting or E-Voting in general elections can solve various administrative problems more efficiently because it can reduce calculation errors that often occur in manual voting.